Determination of Monthly Term Health Insurance Premiums for Individuals Based on Gender - Siahaan, Roy Donald Pangeran (International Journal of Quantitative Research and Modeling, 2025)
Health is one of the important aspects of human life, and protection against health risks is a necessity for every society. Health insurance is a solution in providing protection against financial risks from health. In its implementation, determining premiums is an important factor for insurance companies in order to cover claims from policyholders. Premiums are money paid by policyholders to insurance companies in order to receive benefits in the future. This study aims to determine the monthly premium for term health insurance which adjusted for each gender using actuarial approach. The premium is determined using the 2023 Indonesian Mortality Table and the Indonesian Morbidity Table I "Critical Illness". Based on this study, it was found that the value of the monthly term health insurance premium will increase if the policyholder's entry age and the insurance contract period increase. This study also found that the premium values for men were greater than the premium and reserve values for women if the policy entry age of the man or woman was over 30 years, in addition, the premium and reserve values for women were greater.